BIOLOGICAL CONTROL OF TERMITES: A BIBLIOMETRIC AND STATE-OF-THE-ART REVIEW (Nativa, 2024)
ABSTRACT: Termites are considered pests and biological control is an environmentally friendly alternative to reduce pesticide contamination. It was aimed with this study to compile the publications indexed in the Scopus platform referring to biological control of termites between 1981 and 2019. A total of 143 publications were found, each of which was read and filtered according to the selection criteria. The studies analyzed were conducted in 16 countries, with the United States leading the way (44%). A total of 55 termite species and seven families were recorded in the papers. For the control agents tested, more than 140 species were identified and classified. Plant insecticides were the most cited, with emphasis on oils and extracts from Azadirachta indica and Chamaecyparis obtusa. It was noted that most research was conducted on a laboratory scale in the form of experimental designs. This may limit more comprehensive discussions of the biological termite control agents tested. Although the use of other control agents is increasing, there is a wide range of insecticides and plant-derived compounds that can be studied.Keywords: pesticides; Xylophagous agente; control agentes; ccosystem engineers; systematic review. Controle biológico de cupins: uma revisão bibliométrica e estado da arte RESUMO: Os cupins são considerados pragas e o controle biológico é uma alternativa ecologicamente correta para reduzir a contaminação por pesticidas. Objetivou-se com este estudo compilar as publicações indexadas na plataforma Scopus referentes ao controle biológico de cupins entre 1981 e 2019. Foram encontradas 143 publicações, cada uma delas foi lida e filtrada de acordo com os critérios de seleção. Os estudos analisados foram realizados em 16 países, com os Estados Unidos liderando (44%). Um total de 55 espécies de cupins e sete famílias foram registradas nos trabalhos. Para os agentes de controle testados, mais de 140 espécies foram identificadas e classificadas. Os inseticidas vegetais foram os mais citados, com ênfase em óleos e extratos das espécies Azadirachta indica e Chamaecyparis obtusa. Foi observado que a maioria das pesquisas foram conduzidas em escala laboratorial na forma de delineamentos experimentais. Isto pode limitar discussões mais aprofundadas sobre os agentes biológicos de controle de cupins testados. Embora o uso de outros agentes de controle esteja aumentando, há uma vasta gama de inseticidas e compostos derivados de plantas que podem ser estudados.Palavras-chave: pesticidas; agente Xilófago; agentes de controle; engenheiros de ecossistema; revisão sistemática.